Background-free room temperature phosphorescence and digital image colorimetry detection of melamine by carbon nitride quantum dots in cellulose matrix with smartphone-based portable device. (1st October 2022) - Kong, Yuelin; Lei, Tiantian; He, Yu; Song, Gongwu
Highlights: CNQDs were embedded in CMC matrix to form CNQDs-CMC film with yellow RTP emission. A smartphone-based miniature device was designed for rapid detection of MEL. It was validated by detection of MEL in milk without fluorescence background. Abstract: Carbon nitride quantum dots (CNQDs) were embedded in the sodium carboxymethyl cellulose (CMC) matrix to form CNQDs-CMC film to explore the room temperature phosphorescence (RTP) of CNQDs, which suppress the non-radiative relaxation process due to the internal hydrogen bonding interactions between CMC and CNQDs. Then, a simple, inexpensive, background-free miniature device integrating with CNQDs-CMC film and smartphone was fabricated for rapid and quantitative detection of melamine (MEL). In the present of MEL, the yellow RTP color of the CNQDs-CMC film was quenched and photographed by the smartphone. The Color Recognizer APP in the smartphone recognized the red (R) value for quantitative detection of MEL. Thus, digital image colorimetry (DIC) determination of MEL was achieved due to the visible RTP color change of CNQDs-CMC film. The smartphone-based miniature device provided a promising platform for the on-site monitoring analytes in the complex matrix including food safety, environmental screening, health monitoring, and disease prevention.